Time-dependent behaviour of 100% recycled coarse aggregate concrete filled steel tubes subjected to high sustained load level. (1st May 2020) - Geng, Yue; Wang, Yuyin; Chen, Jie; Zhao, Muzi
Highlights: Nonlinear creep test on circular RACFST stub columns. Influence of the RCA on the nonlinear creep of circular CFST. Variation of confinement effects with time for RACFST. Abstract: Encasing recycled aggregate concrete (RAC) in circular steel tube can improve the mechanical behaviours of the RAC without considerably increasing the cost. The confinement effects, which significantly increase the strength and the ductility of the RAC, also influence the nonlinear creep behaviour of RAC, which has not been well investigated. This paper presented nonlinear creep tests on recycled concrete filled steel tubes (RACFST) for up to 500 days. The load level varied between 0.41 and 0.79. Two concrete strengths were included in the tests (i.e. 30 MPa and 50 MPa). All these members used 100% of the recycled coarse aggregates (RCA) and have the steel ratio (the ratio of the steel area over the concrete area) of 0.08. The tested time-dependent deformations were compared against those reported for the circular CFST members to investigate how the full use of RCA would influence the nonlinear creep behaviour of the composite sections. The confinement effects were also carefully monitored during the long-term tests. It was found that the nonlinear creep can increase the creep coefficient of the RACFST members by 52%–115%, which needs to be carefully considered in the design. Confined by steel tubes, the encased RAC could stand for up to 500 days without creep failure under the stress level of 0.78–0.98 f cm, where f cm is the uniaxial strength of the RAC. The use of recycled aggregates can considerably increase the nonlinear creep effects by up to 22%, and such influence increased with the sustained loading level to the maximum value at the stress level of approximately 0.68 and then started to decrease.